Analisa Denyut Jantung Menggunakan Aplikasi Mobile Self Integrated BioInformatics System - Rani Purbaningtyas (Jurnal Teknologi Informasi dan Terapan, 2019)
Heart disease is still ranked first in the WHO most dangerous and deadly disease in the world. This is also influenced by the individual's reluctance to check his heart condition routinely. So we need an application that is able to help overcome this. SIBioS application is a mobile-based application that functions to analyze heart rate. SIBioS is useful to help with the initial diagnosis of the presence or absence of cardiovascular disorders in individuals. The method applied for data analysis in SIBioS applications is case-based reasoning. Each heart rate data obtained will be calculated the degree of closeness of the distance to the heart rate contained in the knowledge base owned. So that the individual's heart rate can be informed. The test results show SIBioS is able to provide information about the status of the heart condition tester in accordance with the real condition of the tester at the time of measurement. In addition to using the right data analysis method, the results of heart rate data analysis are also influenced by the smartwatch device which is used as a media for tapping heart rate data, gender, age, daily physical activity, individual professional status, and supporting factors when measuring the resting heart rate. Case-based reasoning analysis methods can be applied to heart rate analysis to determine the condition of a person's heart under normal conditions or the presence of cardiovascular disorders. The physical activity recommendations given by the system are determined based on the individual's heart condition.